2012
DOI: 10.3892/etm.2012.735
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse-related severe acute pancreatitis with rhabdomyolysis complications

Abstract: Abstract. Non-traumatic rhabdomyolysis is a rare complication of acute pancreatitis. One of the major risk factors of both acute pancreatitis and rhabdomyolysis is alcohol abuse. However, only a few studies have reported the prognosis and association of severe acute pancreatitis (SAP) and rhabdomyolysis in alcohol abuse patients. In the present study, we report two cases presenting with SAP complicated by rhabdomyolysis following high-dose alcohol intake. The disease onset, clinical manifestations, laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Karachaliou et al described a case report of a 64-year-old woman whose increased CK levels normalized throughout hospitalization in total of 12 days ( 23 ). Mao-Sheng Su et al published a case report about an alcoholic-cause AP but whose highly increased CK were related to another comorbidity – rhabdomyolysis ( 24 ). Shabestari et al described in their case report about the AP patients whose condition was caused by the anabolic steroids resulting in the acute increase of CK followed by high amylase levels ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Karachaliou et al described a case report of a 64-year-old woman whose increased CK levels normalized throughout hospitalization in total of 12 days ( 23 ). Mao-Sheng Su et al published a case report about an alcoholic-cause AP but whose highly increased CK were related to another comorbidity – rhabdomyolysis ( 24 ). Shabestari et al described in their case report about the AP patients whose condition was caused by the anabolic steroids resulting in the acute increase of CK followed by high amylase levels ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bertschy et al reported a patient who developed rhabdomyolysis after moderate alcohol abuse. Su et al reported two cases of pancreatitis with rhabdomyolysis also related to alcohol abuse. Therefore, it is likely that alcohol assumption may contribute to rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol causes rhabdomyolysis through disruption of Adenosine triphosphates pump function, break down of the muscle membrane, alteration of the sarcoplasmic reticulum, sodium permeability and disrupting calcium homeostasis, inducing cytokine releasing the levels of "interleukin (IL) 1, IL-2, IL-6", and" tumor necrosis factor α" (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%